2020
DOI: 10.1097/aco.0000000000000865
|View full text |Cite
|
Sign up to set email alerts
|

The opioid epidemic in pediatrics: a 2020 update

Abstract: Purpose of review Over the last 3 years and for the first time in 60 years, life expectancy in the United States has declined across all racial groups primarily because of drug overdoses, alcohol abuse, and suicide. A public health response to the opioid crisis must expand its focus to more broadly include children, adolescents, and young adults while increasing efforts toward preventing new cases of opioid addiction, early identification of individuals with opioid-abuse disorder, and ensuring acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 74 publications
0
22
0
Order By: Relevance
“…This case was managed before the 2020 Surviving Sepsis Campaign International Guidelines [12] were published; therefore inotropes were initiated with dopamine, though adrenaline infusion followed quickly. Although opioid intoxication is not only seen in people with opioid addiction, current studies concerning the pediatric population on opioid intoxication mainly focus on opioid overdose in adolescents within the context of the opioid epidemic [13] or withdrawal management in neonatal abstinence syndrome [14].…”
Section: Discussionmentioning
confidence: 99%
“…This case was managed before the 2020 Surviving Sepsis Campaign International Guidelines [12] were published; therefore inotropes were initiated with dopamine, though adrenaline infusion followed quickly. Although opioid intoxication is not only seen in people with opioid addiction, current studies concerning the pediatric population on opioid intoxication mainly focus on opioid overdose in adolescents within the context of the opioid epidemic [13] or withdrawal management in neonatal abstinence syndrome [14].…”
Section: Discussionmentioning
confidence: 99%
“…Although drug overdoses represent a smaller portion of suicides in adolescents, many patients are prescribed medications to treat pain after traumatic injuries, and it is important to integrate opioid misuse prevention strategies and counseling for patients and their caregivers since opioids increase the risk of misuse, overdose, and suicide [ 50 ]. There is also a valid concern that many opioid overdose deaths are misclassified as unintentional overdose; therefore, the burden of suicide is likely underappreciated [ 90 ]. There is more guidance and recommendations provided about pain management strategies to increase utilization of non-opioid analgesia and reduce doses of outpatient prescriptions [ 50 , 91 ].…”
Section: Evidence-based Practices For Trauma Centersmentioning
confidence: 99%
“…There is increasing recognition of the impact of prescription opioid overutilization as a key factor in the current opioid crisis. Opioid substance abuse and addiction among teenagers, and subsequent overdoses from the drug are typically initiated from leftover opioids that were originally prescribed appropriately for pain 18…”
mentioning
confidence: 99%
“…Opioid substance abuse and addiction among teenagers, and subsequent overdoses from the drug are typically initiated from leftover opioids that were originally prescribed appropriately for pain. 18 Getz et al 19 recently reported about opioid utilization in pediatric patients newly diagnosed with acute myeloid leukemia and found differences in opioid utilization by age and race, and moderate variability of prevalence of opioid utilization across institutions. Orsey et al 20 reported on the variation of opioids prescribed to pediatric oncology patients during their last week of life and found significant differences among hospitals, even after adjusting for clinical patient's characteristics.…”
mentioning
confidence: 99%